Problemy badań czechosłowackiej kultury popularnej - Kulmiński, Robert (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2015)
The beginning of the 21st century gave the Czech reflection on Czechoslovakian culture a new impulse which resulted in many publications and conferences dedicated to this phenomenon. Yet we are still facing an emerging reflection. If we were to disregard singular papers written from the perspective of historical, historico-literary or media studies, the studies of Czechoslovakian popular culture are just starting to develop. In my article, based on conducted research and analyses, I would like to highlight some methodological problems faced by the reflection on the phenomena of Czechoslovakian popular culture which emerges in the Czech Republic, which are the result of the conditions of the communist regime and of – often too overwhelming – Western European and America tradition which offers tools that are not always suited to the specificity of the reign of the centrally planned economy and the Central European space.
Keywords: Czechoslovak popular culture; Miss Czechoslovakia; Czech literature; Czech film